Penerapan Metode Uswah (Keteladanan) dalam Pendidikan Anak Yatim di Pondok Pesantren Uwais Al-Qorni Bogor: Application of the Uswah (Exemplary) Method in the Education of Orphans at the Uwais Al-Qorni Islamic Boarding School Bogor - Unang Sodikin; Endin Mujahidin; Samsuddin, Samsuddin (Litera Academica Publishing, 2025)
This article discusses the application of the exemplary education method (uswah) at Uwais Al-Qorn Boarding School, which is effective in shaping the character of yatama through habituation, motivation, rule enforcement, and prayer. The study employs a qualitative descriptive interpretive approach, with data collection through interviews and observation. The findings of this study indicate that the uswah method at Uwais Al-Qorni Pesantren not only deepens the spiritual and emotional understanding of the students but also strengthens their discipline and responsibility. Consistent habituation, constructive motivation, and strict rule enforcement, combined with prayer, are key factors in preparing students to face life's challenges. The implications of this study suggest that the application of a holistic, structured education method grounded in Islamic values can make a significant contribution to shaping a generation that is strong, independent, and of noble character. This approach is not only relevant for pesantren but can also be applied in various educational institutions to cultivate better character development in students and prepare them to face the dynamics of modern life.